2020
DOI: 10.1021/acs.jafc.0c02034
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Mobility-Based Liquid Chromatography–Mass Spectrometry Quantitation of Taste-Enhancing Octadecadien-12-ynoic Acids in Mushrooms

Abstract: For the accurate quantitation of kokumi-enhancing and bitter-tasting octadecadien-12-ynoic and octadecadienoic acids in chanterelles (Cantharellus cibarius Fr.), a sensitive ultra-high-performance liquid chromatography−differential ion mobility spectrometry−tandem mass spectrometry method was developed. On the basis of these quantitative data and the taste thresholds, dose-over-threshold factors were calculated to determine the contribution of these sensometabolites to the kokumi and bitter taste of chanterell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Additionally, the DMS technique was implemented to overcome the mass transitions’ spectral overlap 295.1 → 171.0 for 9-HODE isomers 5 and 6 and 295.1 → 195.0 for 13-HODE isomers 7 and 8 , respectively. In the past, DMS had already been used to enhance the selectivity for analyzing isobaric and isomeric substances. ,,, …”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, the DMS technique was implemented to overcome the mass transitions’ spectral overlap 295.1 → 171.0 for 9-HODE isomers 5 and 6 and 295.1 → 195.0 for 13-HODE isomers 7 and 8 , respectively. In the past, DMS had already been used to enhance the selectivity for analyzing isobaric and isomeric substances. ,,, …”
Section: Results and Discussionmentioning
confidence: 99%
“…In the DMS cell, the SV shifts the ion trajectories in the DMS cell and prevents the ions from entering the MS/MS system. This voltage is negated by the CoVa compound-specific parameter that compensates for the SV-dependent shift of an ion trajectory for specific ions to enter the MS. Several parameters, for example, the temperature or the use and type of a chemical modifier, affect the DMS cell’s gas equilibrium. ,, Based on Mittermeier et al (2020), each parameter’s optimization was performed on the column individually . Accordingly, each HODE isomer ( 5–8 ) was injected separately into the UHPLC–DMS–MS/MS system, and the CoV was ramped from −30 to 15 V for a fixed set of SVs (500, 1000, 1500, 2000, 2500, 3000, and 3500 V).…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 The use of ion mobility devices provides an additional separation dimension for resolving complex chemical mixtures with structural similarity. Mittermeier et al developed a LC−ESI−IMS method for quantitation of sensometabolites in chanterelles and other mushrooms, 32 in which nitrogen was used as the carrier gas and 2-propanol was used as the gas modifier during the IMS analysis. The study found that octadecadien-12-ynoic acids, especially (10E,14Z)-9-hydroperoxy-10,14-octadecadien-12-ynoic acid, are the major taste-modulating compounds in chanterelles, which were strongly affected by storage and thermal treatment.…”
Section: Separation Techniquesmentioning
confidence: 99%